Reproduction of Hypoptopoma inexspectatum (Holmberg, 1893) (Siluriformes, Loricariidae) in the Southern Pantanal Floodplain, Upper Paraguay River Basin, Brazil - Pereira,M. J. (2021)
Abstract This work aimed to describe the reproductive biology of Hypoptopoma inexspectatum in southern Pantanal. A total of 538 individuals were sampled and analyzed from February 2009 through January 2011 in southern Pantanal. We did not observe differences in sex-ratio, and both sexes presented positive allometric length/weight relationship (LWR). Reproduction occurs mainly from January to February. Females reached first maturation (L50) with 37.80 mm and males with 45.80 mm. Absolute fecundity is estimated in mean=177.43 (sd±127.06) oocytes and relative fecundity in 3.12 (sd±2.23) oocytes/mg. Fecundity is positively correlated with standard length (Spearman r= 0.43; p=0.013), and total spawning is a used spawning strategy for H. inexspectatum.